Study of pesticide use on bitter gourd production at Jashore district - Hajong, P; Rahman, MS; Islam, MA; Biswas, GC (International Journal of Agricultural Research, Innovation and Technology, 2021)
The study was designed to assess the extent of pesticide use and profitability of bitter gourd production at farm level in selected areas of Jashore district during January-May, 2019. Average farm size was 0.79 ha and average bitter gourd cultivated area per farmer was 0.07 ha. Most of the farmer cultivated local variety, which is called Gajkorola and some farmer cultivated hybrid korola such as Gonggajoli, Tia and BARI Korola-1 variety. About ninety-nine percent farmers sprayed insecticides and fungicides in their fields to protect crops from different insect pests and diseases. Thirty-nine percent farmers used pheromone trap for crop protection. A farmer averagely used 11.19 times spray in their fields and its range was 5-18 times in a season. The average yield of bitter gourd was 16.74 t ha-1 for non-IPM farmer and 16.16 t ha-1 for IPM farmer. The average total cost of production of bitter gourd was Tk. 203984 ha-1 for non-IPM farmer and Tk. 191246 ha-1 for IPM farmer. Gross return was Tk. 389705 ha-1 and net return was Tk. 185721 ha-1 for non-IPM farmer. While, gross return of IPM farmer was Tk. 360828 ha-1 and net return was Tk. 169582 ha-1. Benefit cost ratio was 1.91 and 1.89 for non-IPM and IPM farmer, respectively that means bitter gourd production was profitable. Cent percent farmer reported that IPM technology was time-consuming method and it was not only the measures to protect pests. Int. J. Agril. Res. Innov. Tech. 10(2): 110-115, December 2020